The impact of early surgical ventricular septal defect repair on parenting behavior and mother-child relationship: a prospective longitudinal study - Hemetsberger, Jonas; Mestermann, Stefan; Nicol, Hannah; Purbojo, Ariawan; Cesnjevar, Robert A.; Kratz, Oliver; Eichler, Anna; Gerlach, Jennifer (Frontiers in Pediatrics, 2024)
Introduction: Many studies have investigated the impact of congenital heart defects (CHD) on child development. However, because CHD not only affects the child and his or her development but, also the entire family, family functioning after pediatric cardiac surgery is of increasing research interest. This prospective childhood-adolescence case-control study aimed to examine differences and changes in parenting behavior and mother-child relationship quality after early surgical repair of an isolated ventricular septum defect (VSD) compared to non-affected controls. Patients and Methods: 39 affected children (M = 7.3 years) with surgically repaired VSD and their mothers were compared with a matched, non-affected control group of 39 mother-child-dyads (M = 7.3 years) during primary school age (t1). At child early adolescence, 24 affected children (M = 12.4 years) and 24 children of the control group (M = 13.2 years) were examined again (t2). Parenting behavior characteristics (t1: mother report; t2: motherand child report) and mother-child relationship quality (t2: child report) were measured by standardized questionnaires. Results: The mother-rated parenting behavior dimensions Involvement (p < .001, η²p = .37), Parental Monitoring (p = .014, η²p = .17) and Corporal Punishment (p < .001, η²p = .57) significantly decreased from t1 to t2 in both cohorts. Responsible Parenting Behavior tended to decrease from t1 to t2 in the control group, while remaining stable in the VSD-group (p = .088, η²p = .09). Independent of the group, higher mother-child relationship quality was associated with more Positive Parenting Behavior (p < .001, η²p = .34), more Involvement (p = .003, η ²p = .22) and fewer Inconsistency (p < .001, η²p = .31) in the child-rating; and more Positive Parenting Behavior in the mother-rating (p = .039, η²p = .10). Conclusion: VSD affected mother-child-dyads were mostly comparable in their parenting behavior characteristics and mother-child relationship quality to non-affected controls. The absence of a decrease in maternal Responsible Parenting Behavior in the VSD group may indicate challenges during the developmental task of autonomy in adolescence.Nevertheless, adaptive family functioning after early pediatric surgical VSD repair seems possible.